Features of surgical tactics in acute cholangitis depending from the mechanism of its development - V. A. Vovk (Сучасні медичні технології)
Purpose of the study. Improvement of acute cholangitis treatment by improving surgical tactics, depending on the mechanisms of acute cholangitis development.